Speech Acts and the Different Perspectives on the Meaning of Very Sorry in the Letter on Hainan Island Incident - Christine Permata Sari (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
This study aims to analyze the types of speech acts in the text and to analyze different perspectives on the meaning very sorry between the United States of America and the People's Republic of China. The object of the study is a letter of saying sorry from the U.S. Ambassador for China Joseph Prueher to the Foreign Minister of the PRC Tang Jiaxuan on the incident in Hainan Island which caused the death of the Chineses pilot and the custody of the aircraft crew and the surveillance aircraft relating the emergency landing without any prior permission. The researcher employed the speech acts theory proposed by Searle (1979) as cited by Wardhaugh (2006) to analyze speech acts types and to obtain the dominant type and the implication used in the text. The strategies of apology by Cohen and Olshtain (1986) as cited by Zhang (2001) were also employed. This study is descriptive qualitative research. The result showed the biggest percentages of the types were expressive and assertive. The researcher also found the different perspectives on the meaning of very sorry between the US and the PRC which led into misunderstanding influenced by the culture. This research benefits the English language learners to understand the meaning of locutions which they hear and to acknowledge the culture influences society perspectives in understanding the meaning especially for non-English speakers.